Civic Engagement Through Critical Action Research: Reflections on Ten Years of Forestaction Nepal Experience - Ojha, Hemant Raj (New Angle: Nepal Journal of Social Science and Public Policy, 2012)
This paper describes a mode of ‘doing civic action’. It is based on the experience of a large NGO in Nepal, ForestAction. It details the method that was developed, termed ‘Critical Action Research’ (CAR). CAR "emphasises learning from practice, collating and communicating critical evidence for transforming policy dialogue while also empowering right holder citizens and their alliances through sharing knowledge counteracting the dominant system". The paper also details the historical and political economic context in which CAR developed, provides examples of how CAR operated at different levels of forest and natural resources governance and outlines the challenges faced by CAR innovators. It suggests ways forward for NGOs wishing to bridge the divide of academic/research, advocacy, and service delivery.